Resto banal : experiências ecosóficas com arte contemporânea - Araujo, Luís Antonio Segadas de (2017)
In artistic experience with remains of the society, the author chooses the lid of plastic bottles as the poetic agent and, with it, immerses in a creative, restless process, in multiple practices in the realms of contemporary art. This object is legitimized as an artwork inside and outside the gallery and leads to a reflection on cities, consumption, social relations, scrap, and the work of artists who produce their works from what is called "garbage". "Felix Guattari's concept of "ecosofia ", which points to three perspectives of a new ecology: environmental, social and mental, supports the discussion."